OPTIMASI FASE GERAK KROMATOGRAFI CAIR KINERJA TINGGI PADA PENETAPAN KADAR PIPERIN BUAH CABE JAWA (Piper Retroofactum Vahl.) - Christina, Odilia Dea; Nurul, Aisiyah; Ina, Ayu (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Piperine is the main alkaloid compound found in various types of pepper, including long pepper (Piper retrofractum Vahl.). Determining the piperine content in natural materials and processed products is important in the context of quality control and pharmaceutical research. The analytical method frequently used for determining piperine content is High-Performance Liquid Chromatography (HPLC). One critical factor in HPLC analysis is the selection and optimization of the mobile phase. This study aims to optimize the mobile phase in HPLC analysis to determine piperine content. The mobile phases used were acetonitrile:methanol:distilled water (60:10:30) and acetonitrile:methanol:distilled water (65:5:30). The results showed that the optimal mobile phase for determining piperine content using HPLC is a mixture of acetonitrile:methanol:distilled water in the ratio of 65:5:30 (v/v)